Promoção de políticas públicas para o desenvolvimento sustentável : um estudo sobre os produtores de uva orgânica no Município de São Marcos-RS - Suzin, Querli Polo (My University, 2017)
Organic agriculture is still not very expressive in Brazil. However, its relevance is growing and, in the case of the Municipality of São Marcos-RS, has been gaining prominence in the national market, from the production of organic grape juice, being the municipality the largest producer in Brazil of this product. The general objective of the present research is to demonstrate the deficiencies faced by the organic producers in the Municipality of San Marcos and to identify public policies that serve as an instrument to foment this segment, promoting sustainable development. The study was carried out from a descriptive research, with a qualitativequantitative approach, with a case study. For the application of the data collection instrument, the total population of organic grape farmers was selected, consisting of 25 interviews and, by sampling, 25 other producers of conventional grape, totaling 50 interviewees. Organic farmers had a higher level of satisfaction than conventional farmers. Several shortcomings have been identified, and the absence of public policies in the sector is the main one. Based on the study, it was possible to identify 21 public policies that could be implemented in the city of São Marcos-RS, seeking to promote organic agriculture, both for existing producers and those who will join the segment. At the end, it was concluded that the objective of the research was fully met, since the needs faced by organic producers in the Municipality of São Marcos were identified and public policies were identified as a tool to promote this segment, promoting local sustainable development.
A agricultura orgânica é ainda pouco expressiva no Brasil. Sua relevância é, no entanto, crescente e, no caso do Município de São Marcos-RS, vem ganhando destaque no mercado nacional a partir da produção de suco de uva orgânico, sendo o município o maior produtor do Brasil deste produto. O objetivo geral da presente pesquisa consiste em demonstrar as carências enfrentadas pelos produtores orgânicos no Município de São Marcos e identificar políticas públicas que sirvam de instrumento para fomentar esse segmento, promovendo a desenvolvimento sustentável. O estudo foi realizado a partir de pesquisa descritiva, de abordagem quali-quantitativa, com estudo de caso. Para a aplicação do instrumento de coleta de dados foi selecionada a população total de agricultores de uva orgânica, consistente em 25 entrevistados e, por amostragem, outros 25 produtores de uva convencional, totalizando 50 produtores entrevistados. Os agricultores orgânicos apresentaram um nível maior de satisfação do que os convencionais. Foram identificadas diversas carências, sendo a ausência de políticas públicas no setor a principal delas. A partir do estudo realizado foi então possível identificar 21 políticas públicas que poderiam ser implementadas no município de São Marcos-RS, buscando promover a agricultura orgânica, tanto para os produtores já existentes, como para aqueles que irão ingressar no segmento. Ao final, concluiu-se que o objetivo da pesquisa foi plenamente atendido, uma vez que foram detectadas as carências enfrentadas pelos produtores orgânicos no Município de São Marcos e identificadas políticas públicas que sirvam de instrumento para fomentar esse segmento, promovendo o desenvolvimento sustentável local e regional.
Keywords: Agricultura orgânica - São Marcos (RS); Política pública; Desenvolvimento sustentável; Organic farming - São Marcos (Brazil); Public policy; Sustainable development